Człowieka portret własny. Karola Wojtyły–Jana Pawła II antropologia adekwatna - STYCZEŃ, Tadeusz (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
From the beginning of philosophy various thinkers have attempted to answer the question of what man is. The author analyzes the answer proposed by Protagoras, who claimed that man is the measure of all things, and observes that it might have been satisfactory for the subsequent generations were it not for Socrates. The latter did not so much oppose Protagoras’s claim as attempted to point to the sine qua non condition determining its reasonableness, and he established that condition by pointing to the objective criterion of truth. According to Protagoras’s interpretation, man is the measure of all things when he re− lies on himself only, while Socrates holds that man is the measure of all things if he relies on the truth about them, itself independent of him. In this light, the Socratic project, expressed by means of the rule: “Know thyself,” aims at self−knowledge obtained in the light of truth, and as such it ultimately aims at shaping righteous conscience. According to Styczeń, the controversy between Protagoras and Socrates is not merely a controversy between two philosophical positions, but also one about the soul of culture, and it continues throughout the entire human history. In fact, it is a controversy about the identity of man. Styczeń believes that Karol Wojtyła–John Paul II is a thoroughly Socratic thinker. He presents Wojtyła as a philosopher who accepts the Socratic view of man and who simultaneously develops this view, pointing to its rootedness in actual moral experience. Within the scope of moral experience lies the experience of guilt which may be explained only by the existence of an objective (veritative) criterion which either commands or prohibits something (moral duty). Thus the experience of guilt simultaneously opens a theological perspective for the philosophical reflection on man. Styczeń concludes by saying that at this point Karol Wojtyła’s philosophical discourse about the human being is complemented by the theology he advanced as Pope John Paul II. The reason is that a human being, who by him− or herself is capable of choosing what offends truth and doing what he or she must not do, is unable to annul the consequences of such a choice and of such actions. The Christian revelation brings the «good news» about the Redeemer of man (Redemptor hominis), who has the power to free man from the guilt that rests on him. The Redeemer is the Son of God, who in order to redeem man became man himself. Summarized by Cezary Ritter Translated by Dorota Chabrajska